On creation Quaestiones disputatae de potentia Dei, Q. 3 - Thomas, Aquinas, Saint, 1225?-1274.; Selner-Wright, S. C. (Susan Canty) (Washington, D.C. : Catholic University of America Press, 2011)
This volume includes a new English translation of Question 3, in which Thomas takes up questions and ideas about divine and human freedom, whether or not the world is created, the problem of evil, the efficacy of creatures, and the status of the developing human embryo. It offers a comprehensive treatment of creation and the metaphysics and anthropology Thomas employs in considering the general creation of the universe and the particular creation of each human being. --
Susan C. Selner-Wright's translation of the critical Leonine edition is intended to make Thomas' contribution to the current discussion more accessible. It constitutes a focused but extended example of Thomas at the height of his intellectual powers. Throughout the text, Selner-Wright directs the reader to Thomas' own sources, related texts elsewhere in Thomas' corpus, and secondary sources. Philosophical notes give background for particular claims or arguments and trace important philosophical principles at work throughout the text. --Book Jacket.
Article 1. Whether God can make something out of nothing -- Article 2. Whether creation is a change -- Article 3. Whether creation is something real in the creature, and, if it is, what it is -- Article 4. Whether the power or even the act of creation is communicable to another -- Article 5. Whether there can be anything that is not created by God -- Article 6. Whether there is only one principle of creation -- Article 7. Whether God works in all the operations of nature -- Article 8. Whether God operates in nature by creating, which is to ask whether creation is -- Mingled with the work of nature -- Article 9. whether the rational soul is brought into being by creation or by the transmission of -- Semen -- Article 10. Whether the rational soul is created in the body or apart from the body -- Article 11. Whether the sensitive or vegetative souls are created or transmitted through the -- Semen -- Article 12. Whether the sensitive or vegetative soul is in the semen from the beginning, when it -- Issues forth -- Article 13. Whether something which is from another can be eternal -- Article 14. Whether that which is from God, differing in essence from him, can have always -- Been -- Article 15. Whether things proceeded from God by natural necessity or by the decree of his will -- Article 16. Whether a multitude can proceed from one first thing -- Article 17. Whether the world has always existed -- Article 18. Whether angels were created before the visible world -- Article 19. Whether angels could have existed before the visible world.
Translated from the Latin.
Includes bibliographical references (p. 185-192) and indexes.
Description based on print version record.
Keywords: God (Christianity) -- Omnipotence -- History of doctrines -- Middle Ages, 600-1500.; Creation -- History of doctrines -- Middle Ages, 600-1500.; RELIGION / Christian Theology / General; Electronic books